Possible in Philosophy - Taillard, Antoine (Cham: Springer International Publishing, 2022)
Within philosophy, the word “possible” is generally used to speak about either of the following. (1) Possibility: the notion that is expressed by sentences such as “It is possible that there are green cats,” “She may become the best surgeon in the city,” and “Our team can win the race.” Among the features of possibility, three are of particular interest to philosophers: it is closely related with necessity, contingency, and actuality; it is not unified, but comes in multiple varieties; it is intuitively linked to conceivability. (2) The possible: the target of sentences expressing a possibility, i.e., whatever is possible. Philosophical inquiry is notably interested in the existence and the nature of possible things. For those who think possible things exist, the challenge is to say how and where. For those who think possible things do not exist, the challenge is to say how sentences stating a possibility can be true.
Keywords: Possibility; Possibility-statements; Possible objects; Conceivability; Modality; Philosophy; Metaphysics